1986
DOI: 10.1148/radiology.160.1.3012630
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal metastases from hepatoma: frequency, distribution, and radiographic features.

Abstract: Over the past 6 years, the authors evaluated 300 patients with hepatoma as part of phase 1 and 2 treatment protocol trials. Analysis of the available clinical data and radiographic studies revealed 22 patients (7.3%) with skeletal metastases demonstrated by radiography, computed tomography (CT), and/or nuclear scintigraphy. The plain film appearance of skeletal metastases from hepatoma was osteolytic in all cases. CT scanning best demonstrated the expansile, destructive nature of these metastases, which were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 0 publications
1
59
0
Order By: Relevance
“…However, osteolytic lesions may not be detected on bone scintigraphy, and it has been known to be the pitfall of bone scintigraphy [25,29]. In this study, all bone metastases from HCC were osteolytic, and the detection rate of bone scintigraphy was low.…”
Section: Discussionmentioning
confidence: 62%
“…However, osteolytic lesions may not be detected on bone scintigraphy, and it has been known to be the pitfall of bone scintigraphy [25,29]. In this study, all bone metastases from HCC were osteolytic, and the detection rate of bone scintigraphy was low.…”
Section: Discussionmentioning
confidence: 62%
“…Soft-tissue masses are unique to BMs of HCC and have been observed in 39%-85.4% of patients [8,[18][19][20] . These Kuhlman et al [13] 1979-1985 300 22 (7.3) Liaw et al [14] 1983-1887 395 20 (5) Katyal et al [15] 1992-1997 403 148 (36.7) 41(10.2) 28 Fukutomi et al [3] 1978-1987 269 12 (4.5) 1988-1997 404 52 (12.9) Natsuizaka et al [5] 1995 soft-tissue masses can replace the normal bone matrix and exhibit expansive growth, frequently within the vertebral body. Paravertebral masses have been shown to grow inward to encapsulate and destroy the bone matrix [18] .…”
Section: Radiological Featuresmentioning
confidence: 95%
“…The incidence of BMs in HCC patients has been reported to be relatively low; 2%-12.9% in clinical studies, and 7.3%-38.5% in patients with extrahepatic metastases (Table 1) [2, 3,5,[13][14][15][16] . However, BM incidences of 10.2% and 12.9% were reported by Katyal et al [15] and Fukutomi et al [3] , respectively, which are higher than previously reported rates.…”
Section: Incidence Of Bmsmentioning
confidence: 99%
See 2 more Smart Citations